Worsening glycemic control in youth with type 2 diabetes during COVID-19 - Bharill, Sonum; Lin, Tyger; Arking, Alexander; Brown, Elizabeth A.; West, Margaret; Busin, Kelly; Magge, Sheela N.; Wolf, Risa M. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Introduction The COVID-19 pandemic has disproportionately affected minority and lower socioeconomic populations, who also have higher rates of type 2 diabetes (T2D). The impact of virtual school, decreased activity level, and worsening food insecurity on pediatric T2D is unknown. The goal of this study was to evaluate weight trends and glycemic control in youth with existing T2D during the COVID-19 pandemic. Methods A retrospective study of youth <21 years of age diagnosed with T2D prior to March 11, 2020 was conducted at an academic pediatric diabetes center to compare glycemic control, weight, and BMI in the year prior to the COVID-19 pandemic (March 2019-2020) to during COVID-19 (March 2020-2021). Paired t-tests and linear mixed effects models were used to analyze changes during this period. Results A total of 63 youth with T2D were included (median age 15.0 (IQR 14-16) years, 59% female, 74.6% black, 14.3% Hispanic, 77.8% with Medicaid insurance). Median duration of diabetes was 0.8 (IQR 0.2-2.0) years. There was no difference in weight or BMI from the pre-COVID-19 period compared to during COVID-19 (Weight: 101.5 v 102.9 kg, p=0.18; BMI: 36.0 v 36.1 kg/m2, p=0.72). Hemoglobin A1c significantly increased during COVID-19 (7.6% vs 8.6%, p=0.0002) Conclusion While hemoglobin A1c increased significantly in youth with T2D during the COVID-19 pandemic, there was no significant change in weight or BMI possibly due to glucosuria associated with hyperglycemia. Youth with T2D are at high risk for diabetes complications, and the worsening glycemic control in this population highlights the need to prioritize close follow-up and disease management to prevent further metabolic decompensation.